Projected Costs and Returns for Sugarcane Production on Mineral Soils of South Florida, 2007-2008 - Fritz M. Roka; Jose Alvarez; Leslie E. Baucum (EDIS)
SC087, a 16-page report by Fritz M. Roka, Jose Alvarez, and Leslie E. Baucum, develops a model enterprise budget that reflects annual costs and returns for a 5,000-acre farm that grows sugarcane on mineral soils. Includes references. Published by the UF Department of Agronomy, September 2009.